IMPLEMENTING AUTHENTIC ASSESSMENT OF CURRICULUM 2013: TEACHERâS PROBLEMS AND SOLUSIONS - Fitriani, Fitriani (Getsempena English Education Journal, 2017)
AbsractCurricullum 2013 requires English teachers to apply authentic assessment as a method of educational measurement. Authentic assessment is an evaluation process involving multiple forms of studentâs performance on instructionally-classroom activities. This assessment contributes to the development of the effective classroom measurement. It encourages students to be more active and helps teacher reflect on their teaching and improve the instruction. Conversly, applying this method effectively is quite challanging. This study was conducted at one of Senior High School in Aceh Barat Daya and aimed at finding the teachersâ problems in implementing authentic assessment based on curriculum 2013 and what efforts she used to overcome the problems. The English teacher and the curriculum coordinator were interviewed and the classroom instruction was observed to gather the data. The result indicated the teachers difficulties included the excessive marking loads, managing valid assessment, monitoring academic dishonesty, and maintaining quality and consistency of marking. in other words, teacher has been implementing authentic assesment as directed in curricullum 2013. However, the English teacher still experienced some constraints during instructional activities so that the assessment process did not run effectively. Therefore, the teacher is expected to extent her insight and creativity to improve the quality of the assessment.Â Keywords: Authentic Assessment, Implementation, Curricullum 2013